2014
DOI: 10.7556/jaoa.2014.003
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Lumbar Somatic Dysfunction and Its Association With Bone Mineral Density

Abstract: A persistence of predominantly left lumbar rotation was observed. Persistent vertebral motion restriction was shown to have an association with final lumbar BMD T scores, and persistent TTA and tenderness were associated with changes in the BMD T scores over 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It seems to be important to identify and treat VD. Indeed, it has been observed that persistent vertebral motion restriction has an association with final lumbar bone mineral density T scores, and persistent tissue texture abnormalities and tenderness are associated with changes in the bone mineral density T scores [23]. Moreover, the osteopathic manipulative treatment could be used during real and simulated spaceflight with manual treatment being used as an alternative method to the ingestion of analgesic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems to be important to identify and treat VD. Indeed, it has been observed that persistent vertebral motion restriction has an association with final lumbar bone mineral density T scores, and persistent tissue texture abnormalities and tenderness are associated with changes in the bone mineral density T scores [23]. Moreover, the osteopathic manipulative treatment could be used during real and simulated spaceflight with manual treatment being used as an alternative method to the ingestion of analgesic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the subjects back pain was unknown to the professional osteopath during the tests to avoid potentially influencing the palpation. The classic osteopathic vertebral manual tests [22, 23] were used in order to identify vertebral somatic dysfunctions (VD). The research of VD is a convergence of clinical information (observation, characteristic of soft tissues, and test of mobility) to identify the dysfunctional zone.…”
Section: Methodsmentioning
confidence: 99%